PENGARUH LITERASI KEUANGAN DAN KONTROL DIRI TERHADAP PERILAKU MENABUNG GENERASI Z - Annisa Nursofia; Yoni Hermawan; Raden Roro Suci Nurdianti (JOURNAL SAINS STUDENT RESEARCH, 2024)
The purpose of this study is to determine the extent to which financial literacy and self-control can influence the saving behavior of Generation Z Kampung Cibogor Hilir Tasikmalaya City both simultaneously and partially. This research is included in quantitative research using the explanatory design survey method. The research population is the entire generation z community of cibogor hilir village, totaling 102 people. The sampling technique used Nonprobability Samp ling technique, namely saturated sampling so that all populations were sampled. The data collection technique is using a questionnaire and the data analysis technique uses the help of the SPSS version 23 progeram. Based on the results of the variable test, it turns out that partially the financial literacy variable cannot affect saving behavior. While the test for the self-control variable is partially influential on saving behavior. Then for the test of financial literacy variables and self-control simultaneously have an influence on saving behavior with a value of 0.217 means that the saving behavior variable variable is influenced by financial literacy and self-control by 21.7% and for the the remaining 78.3% is influenced by other factors.